2018
DOI: 10.1038/s41467-018-06996-3
|View full text |Cite
|
Sign up to set email alerts
|

A perivascular niche for multipotent progenitors in the fetal testis

Abstract: Androgens responsible for male sexual differentiation in utero are produced by Leydig cells in the fetal testicular interstitium. Leydig cells rarely proliferate and, hence, rely on constant differentiation of interstitial progenitors to increase their number during fetal development. The cellular origins of fetal Leydig progenitors and how they are maintained remain largely unknown. Here we show that Notch-active, Nestin-positive perivascular cells in the fetal testis are a multipotent progenitor population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(125 citation statements)
references
References 69 publications
(128 reference statements)
5
119
1
Order By: Relevance
“…Multiple interstitial cell (CD90/PDGFRA/CoupTFII/Nes) populations can re-enter the cell cycle upon EDS-induced Leydig cell death. This suggests that the interstitial compartment contains a reserve Leydig or a general somatic cell progenitor population that can be activated in response to damage (Chen et al, 1996;Chen et al, 2010;Davidoff et al, 2004;Ge et al, 2006;Jiang et al, 2014;Kilcoyne et al, 2014;Kumar and DeFalco, 2018;Landreh et al, 2013;Qin et al, 2008). However, whether the reported molecular markers are expressed universally by a single population of Leydig stem cells or by distinct cell populations that all have the ability to regenerate remains difficult to tease apart.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple interstitial cell (CD90/PDGFRA/CoupTFII/Nes) populations can re-enter the cell cycle upon EDS-induced Leydig cell death. This suggests that the interstitial compartment contains a reserve Leydig or a general somatic cell progenitor population that can be activated in response to damage (Chen et al, 1996;Chen et al, 2010;Davidoff et al, 2004;Ge et al, 2006;Jiang et al, 2014;Kilcoyne et al, 2014;Kumar and DeFalco, 2018;Landreh et al, 2013;Qin et al, 2008). However, whether the reported molecular markers are expressed universally by a single population of Leydig stem cells or by distinct cell populations that all have the ability to regenerate remains difficult to tease apart.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether the reported molecular markers are expressed universally by a single population of Leydig stem cells or by distinct cell populations that all have the ability to regenerate remains difficult to tease apart. This is due to the difficulty of performing single-cell transplantation and reconstitution experiments in the testis and the lack of multiplexed molecular barcoding tools for lineage tracing (Kumar and DeFalco, 2018;Rotgers et al, 2018;Shima et al, 2018). It is also unclear if a common somatic progenitor could give rise to additional cell types that persists in the adult, and what the role of such stem/progenitors would be in the normal adult testis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that FLCs were developed from stem Leydig cells [8,24]. Stem Leydig cells in the fetal testis are spindle-shaped and express NR2F2, also called COUP-TFII [8,[24][25][26]. We used NR2F2 as the biomarker to identify the stem Leydig cell and SOX9 as the biomarker to draw a boundary for the seminiferous cord.…”
Section: Measurement Of Stem Leydig Cell Numbermentioning
confidence: 99%
“…The vascular niche is also important for the regulation of the steroidogenic progenitors that give rise to Leydig cells (Tang et al 2008, Defalco et al 2013. These progenitors arise both from the CE and from specialized cells along the gonad-mesonephros border (Defalco et al 2011, Kumar & DeFalco 2018.…”
Section: Recruitment Of Other Cell Types In the Gonadmentioning
confidence: 99%